Terminological database to be used as an aid to translating and translator training - Araújo, Luzia (TradTerm, 2002)
This paper describes a termbank (COMEX) dedicated to foreign trade terminology in Brazilian Portuguese, English, and Spanish. Initially, a relational database was designed specially for storage and management of terminological data. The database is PC-based and was developed using Microsoft Access®. Later, an attempt was made to transfer the already stored data to the terminology-oriented MultiTerm® database. In this work, both environments are described and selected data categories are illustrated by means of some terminological record samples given. It is expected that the contents of COMEX can be used as an aid to translation, while the design principles and structure can be used to teach terminology to translation students. The use of the database shall help students to get familiarised with terminological tools for translators and also with the design and building of terminology management systems applied to their profession.